2021
DOI: 10.1007/s00439-021-02259-2
|View full text |Cite
|
Sign up to set email alerts
|

Intronic variant in POU1F1 associated with canine pituitary dwarfism

Abstract: The anterior pituitary gland secretes several endocrine hormones, essential for growth, reproduction and other basic physiological functions. Abnormal development or function of the pituitary gland leads to isolated or combined pituitary hormone deficiency (CPHD). At least 30 genes have been associated with human CPHD, including many transcription factors, such as POU1F1. CPHD occurs spontaneously also in mice and dogs. Two affected breeds have been reported in dogs: German Shepherds with a splice defect in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…We were very fortunate to have received several submissions from the prolific canine research laboratory of Hannes Lohi (Niskanen et al 2021;Kyöstilä et al 2021;Kaukonen et al 2021;Hytönen et al 2021a,b). In the first paper, Niskanen et al (2021) investigated the known variant in DVL2 associated with kinked tails and brachycephaly in bulldog breeds in an additional 1954 dogs from 15 breeds.…”
Section: Novel Findings Identified For Inherited Diseases In Dogsmentioning
confidence: 99%
See 1 more Smart Citation
“…We were very fortunate to have received several submissions from the prolific canine research laboratory of Hannes Lohi (Niskanen et al 2021;Kyöstilä et al 2021;Kaukonen et al 2021;Hytönen et al 2021a,b). In the first paper, Niskanen et al (2021) investigated the known variant in DVL2 associated with kinked tails and brachycephaly in bulldog breeds in an additional 1954 dogs from 15 breeds.…”
Section: Novel Findings Identified For Inherited Diseases In Dogsmentioning
confidence: 99%
“…A genetic cause of canine pituitary dwarfism was previously known for German shepherd dogs. In this special issue, Kyöstilä et al (2021) identified a novel homozygous variant in the POU1F1 gene in affected Karelian Bear dogs. After screening more than 8000 dogs from 207 breeds, only a related breed, Lapponian Herder, was found to also carry this mutation at a low frequency.…”
Section: Novel Findings Identified For Inherited Diseases In Dogsmentioning
confidence: 99%
“…Dwarfism in dogs is due to spontaneous mutations in Lhx3 that are often caused by the shortening of a DNA repeat sequence in intron 5 and is often seen in breeds such as the German Shepherd, Dog Salos, and the Czechoslovakian Wolfdog [ 12 ]. These mutations typically exhibit autosomal recessive inheritance [ 11 , 13 , 14 ]. However, to date, the genetic basis for the differences in body size among the three Japanese dog breeds is not known.…”
Section: Introductionmentioning
confidence: 99%
“…The canine genome exhibits more homology to the human genome than rodents [24], typically used in DCM modeling [25]. Intrabreed mapping approaches resemble population-specific GWASs in human cohorts, and the high breed-specific prevalence of disorders, genetic homogeneity, and extensive linkage disequilibrium enable remarkably well-powered studies in Mendelian diseases [24,[26][27][28][29][30][31]. However, previous attempts to dissect the complex genetic background of DCM in Dobermanns have been limited by inadequate sample sizes or inconclusive functional follow-up, leading to contradictive findings and thus warranting the need for a more extensive and comprehensive study [32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%